Positive Affirmation of Midwives Regarding Antenatal Care Compliance Midwife To Compliance Antenatal Care Integrated In Tambak Bawean Gresik Community Health Center - Hairiya Yuliani Rahman (Journal of Health Science Community, 2025)
Low compliance of pregnant women in carrying out integrated antenatal care results in low early detection of pregnancy complications. The purpose of this study was to analyze the positive affirmation of midwives towards compliance with integrated antenatal care at the Tambak Bawean Gresik Health Center. This uses a design pre experiment Intact-Group Comparison . The population in this study amounted to 30 respondents. The sample in this study were all pregnant women who did not undergo integrated ANC at the Tambak Bawean Gresik Health Center using accidental sampling techniques . Data collection used questionnaires and SOPs and were analyzed using the independent t-statistical test with a significance level of α = 0.05. Most of the respondents in the intervention group were compliant in performing ANC, namely 8 (53.3%) respondents. Most of the respondents in the control group were compliant in performing ANC, namely 8 (53.3%) respondents. The results of the T-test obtained a significant p-value: 0.040 <α=0.05, meaning that there is an effect of providing positive affirmation on ANC compliance at the Tambak Bawean Health Center. Affirmation positive midwife can give calm And comfort for Mother pregnant, through the method of releasing negative energy and channeling positive suggestions to the patient, so that the pregnant woman feels comfortable and ready to face pregnancy and childbirth.